Nobiletin, sinensetin, and tangeretin are the main perpetrators in clementines provoking food-drug interactions in vitro - Weiß, Johanna; Gattuso, Giuseppe; Barreca, Davide; Haefeli, Walter E. (Food chemistry, 2020)
For clementine juice, previous data indicate a possible food-drug interaction with substrates of key enzymes responsible for drug metabolism (i.e. cytochrome P450 [CYP] 3A4, CYP1A2). However, which compounds in clementine juice are responsible for these effects are unknown. Therefore, we aimed to identify the compounds in clementine juice provoking metabolic enzyme inhibition or induction. The results demonstrated that the flavonoid fraction of clementine juice provoked induction of several genes and inhibition of both CYP3A4 and CYP1A2, matching effects observed with whole clementine juice. CYP1A2 inhibition and induction can most likely be attributed to nobiletin, sinensetin, and tangeretin. Tangeretin was the only compound causing CYP3A4 induction while CYP3A4 inhibition was most likely the result of additive or synergistic effects caused by several compounds. Thus, whenever evaluating the clinical relevance of clementine interactions, flavonoid contents should be reported because these might explain differences between cultivars and harvests.